2019
DOI: 10.1007/s00442-019-04352-w
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparasitoids exploit herbivore-induced plant volatiles during host location to assess host quality and non-host identity

Abstract: Although consumers often rely on chemical information to optimize their foraging strategies, it is poorly understood how top carnivores above the third trophic level find resources in heterogeneous environments. Hyperparasitoids are a common group of organisms in the fourth trophic level that lay their eggs in or on the body of other parasitoid hosts. Such top carnivores use herbivore-induced plant volatiles (HIPVs) to find caterpillars containing parasitoid host larvae. Hyperparasitoids forage in complex envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…elicited a significant attractive response in the hyperparasitoid. Hence, this suggests that the olfactory response of primary and secondary parasitoids towards mVOCs is different, as has also been found for HIPVs (Cusumano et al, ; Poelman et al, ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…elicited a significant attractive response in the hyperparasitoid. Hence, this suggests that the olfactory response of primary and secondary parasitoids towards mVOCs is different, as has also been found for HIPVs (Cusumano et al, ; Poelman et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, little is known about whether and how mVOCs mediate insect behaviour across trophic levels. Previous studies on plant–insect interactions have shown that herbivore‐induced plant volatiles (HIPVs) are an important source of information mediating multitrophic interactions (Dicke & Baldwin, ; van Oudenhove, Mailleret, & Fauvergue, ), not only attracting primary parasitoids but also mediating the behavioural response of secondary parasitoids (also referred to as ‘hyperparasitoids’ having primary parasitoids as their host; Cusumano, Harvey, Dicke, & Poelman, ; Poelman et al, ). Virtually nothing is known so far on the role of microbial volatiles in the chemical ecology of hyperparasitoids.…”
Section: Introductionmentioning
confidence: 99%
“…However, the higher presence of Eupelmus spp. could also be linked to variations in emissions of herbivore-induced plant volatiles in response to thermal stress [78].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of the HIPV blend changes according to the parasitism status of the attacking herbivore, allowing hyperparasitoids to locate their hosts. Interestingly, HIPV attraction of L. nana occurs regardless of the host caterpillars in which C. glomerata parasitoid larvae develop ( Pieris brassicae or P. rapae ), showing that the parasitoid signature overrules herbivore identity in this system . Lysibia nana and also Pteromalus semotus are attracted to HIPVs induced by parasitized caterpillars on different cabbage cultivars and both hyperparasitoids preferred cultivars that also are more attractive to their primary parasitoid host C. glomerata …”
Section: Infochemicals That Can Be Used To Manipulate Hyperparasitoidmentioning
confidence: 93%
“…More recently, increasing attention has been paid to life‐history traits of hyperparasitoids that affect hyperparasitoid reproduction and hence fitness, such as development and host‐feeding . Progress has also been made in understanding hyperparasitoid behavior, in particular host‐ and mate‐finding, which are mainly guided by chemical cues (infochemicals) . The idea of manipulating hyperparasitoids to enhance biological control was put forward more than two decades ago, but recent progress in chemical ecology makes it possible now to develop truly eco‐friendly pest control, including strategies for managing hyperparasitoids.…”
Section: Introductionmentioning
confidence: 99%